Exploration Of Multicultural Values Of Literation Activities Community In Pamekasan District As A Basis For Character Education - Ria Kasanova; Syaiful Syaiful; Muhammad Rudiyanto; Sri Widjajanti (EDUTECH, 2021)
Multicultural values are the answer to the diversity of society and the demands of equal rights for every citizen. Another aspect of multicultural values is that development provides multiple perspectives and concerns. Learning about multiculturalism cannot be separated from the existence of society itself, because they play a major role in the series of life, it is natural that the government tries to improve the quality of literacy every year. Despite various efforts, the packaging has not produced clear results. On the other hand, the process of learning history as a kind of understanding and knowledge can be a source of inspiration and can foster a sense of nationality and a sense of responsibility towards students as citizens. Therefore, it is possible to instill a spirit of nationalism in the younger generation among the youth. This situation states that if there is no idealism regarding the homeland and nation, the appreciation of the state and nation will feel shallow, especially for Indonesia as a multi-ethnic country. This type of research is a qualitative method designed to reveal events based on actual conditions. The implementation of this research was carried out in the city of Pamekasan, Pamekasan Regency, East Java. The main information provider is the community of literacy activists in Pamekasan District. Data collection techniques used: observation and interviews, while data analysis techniques used 1) data collection; 2) data reduction; 3) data presentation, and 4) Conclude. The contribution of the literacy community in Pamekasan district is to open the understanding and application of multicultural values to youth and the community of Pamekasan district, especially for students and students.